Method for preparing high-purity silica sol by purifying common silica sol and high-purity silica sol
Through the additive stabilization and multi-step ion exchange process, the metal impurities content in the silica sol has been successfully reduced, and the problems of high-purity silicon sol production cost and difficulty in purification are solved, and the stable preparation of high-purity silicon sol and high-end market application are achieved.
Patent Information
- Application Number
- CN202411941964.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-15
AI Technical Summary
The existing high-purity silicon sols have high production costs and high purification difficulty, and the system is unstable during purification, making it difficult to meet the high-end market demand for high-purity silicon sols in the CMP field.
The order of additive stabilization-cation exchange-acidification-cation exchange-anion exchange-anion exchange is adopted to gradually reduce the metal impurity content in the silica sol to prepare a high-purity silicon sol through the use of high-purity strong acid cation exchange resin and strong alkaline anion exchange resin.
The metal impurities content in the silica sol has been significantly reduced, and the single metal impurities are less than 2ppm, the process is stable, and the batch repetition stability is high, which reduces production costs.
Smart Images

Figure BDA0005212736460000061 
Figure BDA0005212736460000101 
Figure BDA0005212736460000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silica sol purification, and specifically relates to a method for preparing high-purity silica sol by purifying ordinary silica sol. Background Art
[0002] Silica sol is a dispersion of nano-scale silicon dioxide particles dispersed in a solvent. It is currently widely used in papermaking, casting, coatings, catalysts and CMP (chemical mechanical polishing) fields. In recent years, with the continuous development of semiconductor technology, silica sol has played an increasingly important role in the CMP field. At present, the manufacturing process of electronic devices is constantly increasing, and the polishing process of semiconductors and other electronic devices also puts forward higher purity requirements for silica sol abrasives. If there are more metal impurities in the silica sol, it may cause metal ions to diffuse into the silicon wafer or electronic devices, causing a short circuit and causing the entire device to fail. Therefore, there are currently strict requirements on the content of metal impurities in silica sol used in the CMP field.
[0003] At present, the commonly used preparation methods of silica sol include the hydrolysis of elemental silicon, the ion exchange method and the hydrolysis of alkoxysilane (Stober preparation method). If the purity is controlled from the raw materials, the elemental silicon method and the ion exchange method are difficult to achieve. Although the hydrolysis of alkoxysilane is easier to control the purity of raw materials and has a relatively mature process, its high-purity raw material cost is relatively high, and the requirements for the environment and equipment during the synthesis process are also extremely high, which also has a large limit on its market price.
[0004] In recent years, many studies have begun to turn to the purification of silica sol. The advantage of this is that it can greatly reduce the cost of raw materials and equipment when preparing silica sol, and silica sol prepared by single silicon method and ion exchange method may also be further applied to the high-end CMP market. Currently, there are many patents reporting on silica sol with reduced ion content.
[0005] Patent CN 102583406 B dynamically mixes the silica sol to be purified with a strong acid and strong base mixed resin, adds a chelating agent and an auxiliary chelating agent under stirring, controls the pH to 1-5, and then obtains a high-purity silica sol. Although the silica sol prepared by this method has a low ion content, it is less economical, and the mixed resin regeneration process is cumbersome and difficult to regenerate.
[0006] Patent CN 104263249 B puts the silica sol to be purified together with a strong acid and strong base mixed resin, stirs them under certain temperature conditions, and adds imidazole and organic acid and base in the process to maintain the stability of the silica sol. This method can only solve the problem that the silica sol is unstable when it is in the gel region at pH = 4-7, and has limited ability to remove metal impurities.
[0007] Patent CN 111334255 B uses water glass as a raw material to produce active silicate through ion exchange reaction. The active silicate is acidified to remove cationic impurities, anions are removed through anion exchange, and purified silicate is obtained through cation exchange. Subsequently, high-purity large-particle silica sol is prepared, and its metal impurity ion content is less than 50ppm. This method has many control steps from synthesis to removal of metal impurities, and the final metal impurity content is still high. Summary of the invention
[0008] In view of the problems of high production cost, high purification difficulty and unstable system during purification of existing high-purity silica sol, the present invention provides an effective method for obtaining high-purity silica sol by subjecting ordinary silica sol to the sequence of auxiliary agent stabilization-cation exchange-acidification-cation exchange-anion exchange, so as to reduce the metal ion content in the ordinary silica sol product and realize its use in high-end fields.
[0009] Another object of the present invention is to provide a high-purity silica sol product prepared by the above-mentioned preparation method.
[0010] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:
[0011] A method for preparing high-purity silica sol by purifying ordinary silica sol comprises the following steps:
[0012] 1) Preparation of high-purity strongly acidic cation exchange resin: non-high-purity strongly acidic cation exchange resin is loaded into an ion exchange column, countercurrently regenerated with an acid solution having a mass fraction of 1%-5%, and then flushed with ultrapure water downstream to obtain a high-purity strongly acidic cation exchange resin;
[0013] 2) Preparation of high-purity strong basic anion exchange resin: non-high-purity strong basic anion exchange resin is loaded into an ion exchange column, countercurrently regenerated with 1%-5% alkali solution by mass fraction, and then flushed with ultrapure water downstream to obtain high-purity strong basic anion exchange resin;
[0014] 3) Adding an auxiliary agent to ordinary silica sol and stirring thoroughly to obtain silica sol A;
[0015] 4) passing silica sol A downstream through a cation exchange column filled with high-purity strongly acidic cation exchange resin to perform ion exchange, and the effluent is silica sol B;
[0016] 5) Adding 5%-10% inorganic acid to silica sol B to adjust the pH of the system, and stirring evenly to obtain silica sol C;
[0017] 6) The silica sol C is passed downstream through a cation exchange column filled with a high-purity strongly acidic cation exchange resin to perform ion exchange, and the effluent is the silica sol D;
[0018] 7) Silica sol D is passed downstream through an anion exchange column filled with high-purity strong alkaline anion exchange resin for ion exchange, and the effluent is high-purity silica sol.
[0019] In the present invention, the acid solution in step 1) and step 2) is hydrochloric acid or sulfuric acid, and the alkali solution is sodium hydroxide or potassium hydroxide;
[0020] Preferably, the linear velocity of the acid or alkali solution regeneration is 1-10 m / h, and the volume ratio of the acid or alkali solution to the wet strongly acidic cation exchange resin or strongly basic anion exchange resin is 5:1-1:1, preferably 4:1-2:1.
[0021] In the present invention, the volume ratio of the total volume of ultrapure water used for rinsing in step 1) and step 2) to the wet strongly acidic cation exchange resin or strongly basic anion exchange resin is 100:1-20:1, preferably 80:1-40:1;
[0022] Preferably, the ratio of the linear velocity of the ultrapure water flushing to the linear velocity of the acid or alkali solution regeneration is 4:1-2:1, preferably 3:1.
[0023] The resin obtained through this purification process has a higher purity, and the pollution during the purification of silica sol is significantly reduced.
[0024] In the present invention, the ultrapure water in step 1) and step 2) is ultrapure deionized water, and preferably the resistivity of the ultrapure deionized water is ≥10 MΩ·cm, and more preferably the resistivity is ≥18.2 MΩ·cm.
[0025] In the present invention, the auxiliary agent in step 3) is selected from one or more of citric acid, tartaric acid, lactic acid, malic acid, maleic acid, malonic acid, lysine, polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, and hexadecyltrimethylammonium bromide, preferably malic acid, lactic acid, or polyethylene glycol. The amount of the auxiliary agent added is 50-2000ppm of the mass of silicon dioxide in ordinary silica sol solution, preferably 500-1000ppm; preferably, the stirring time after adding the auxiliary agent is 0.1-10h, preferably 1-2h. Silica sol is in an unstable gel region at pH = 4-7, and it is easy to form a gel when passing through an ion exchange resin. The addition of the auxiliary agent is conducive to the stability of the silica sol.
[0026] In the present invention, the temperature during ion exchange in step 4), step 6) and step 7) is controlled at 25-60°C, preferably 40-50°C; preferably, the liquid flow rate during downstream flow is controlled at 1-20m / h.
[0027] In the present invention, the inorganic acid described in step 5) should be selected from any one of hydrochloric acid, sulfuric acid or nitric acid, preferably hydrochloric acid. The inorganic acid is used to adjust the system pH to 1.0-3.0, preferably 1.5-2.0; preferably, the stirring time after adjusting the system pH is 0.1-10h, preferably 2-4h. The acidification of this step is very necessary. After the first cationic resin exchange, the silica sol still has a certain amount of metal impurities, especially high-valent metals such as aluminum, iron, and nickel that are easily hydrated. Lowering the system pH to below 3 can free such metal ions in the form of hydrates, and then be fully exchanged in the second cationic exchange.
[0028] Another aspect of the present invention provides a high-purity silica sol prepared by the above method, wherein the silicon dioxide concentration of the high-purity silica sol is 10-50wt%, the particle size is 10-300nm, and the single metal impurity is less than 2ppm.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The method of the present invention uses an external auxiliary agent to stabilize ordinary silica sol with high metal impurities, thereby solving the problem of system instability during silica sol purification. Subsequently, the silica sol is treated with cation exchange-acidification-cation exchange-anion to prepare high-purity silica sol. The single metal impurity in the obtained high-purity silica sol is less than 2ppm, the process is stable and the batch repetition stability is high, which is significantly improved compared with the existing method. DETAILED DESCRIPTION
[0031] In order to better understand the technical solution of the present invention, the preparation method of the present invention is further explained below through more specific examples, but it does not constitute any limitation.
[0032] A method for preparing high-purity silica sol by purifying ordinary silica sol comprises the following steps:
[0033] 1) Preparation of high-purity strongly acidic cation exchange resin: Place commercially available common (non-high-purity) strongly acidic cation exchange resin into an ion exchange column, regenerate it by countercurrent flushing with 1%-5% hydrochloric acid or sulfuric acid by mass fraction, and then continuously flush it downstream with ultrapure deionized water to obtain a high-purity strongly acidic cation exchange resin.
[0034] 2) Preparation of high-purity strong basic anion exchange resin: Place commercially available common (non-high-purity) strong basic anion exchange resin into an ion exchange column, flush it with 1%-5% sodium hydroxide or potassium hydroxide in reverse flow for regeneration, and then flush it with ultrapure deionized water in downstream for continuous flushing to obtain high-purity strong basic anion exchange resin.
[0035] 3) Adding a proper amount of additives to ordinary silica sol with a metal ion content exceeding 5000 ppm, and stirring for a certain period of time to obtain silica sol A.
[0036] 4) Silica sol A is flowed downstream through a cation exchange column at a certain temperature and flow rate, and the effluent is silica sol B.
[0037] 5) Adding an inorganic acid with a concentration of 5% to 10% to silica sol B to adjust the pH of the system to a certain value, and stirring for a certain period of time to obtain silica sol C;
[0038] 6) Silica sol C is passed downstream through a cation exchange column at a certain temperature and flow rate, and the effluent is silica sol D.
[0039] 7) The silica sol D is passed downstream through an anion exchange column at a certain temperature and flow rate, and the effluent is high-purity silica sol.
[0040] The acid (alkali) regeneration linear speed in step 1) and step 2) is 1-10 m / h, such as 1 m / h, 2 m / h, 3 m / h, 4 m / h, 5 m / h, 6 m / h, 7 m / h, 8 m / h, 9 m / h, 10 m / h, etc.; the volume ratio of the regenerated acid (alkali) to the wet strongly acidic cation (strongly basic anion) exchange resin is 5:1-1:1, such as 5:1, 4.5:1, 4:1, 3.5:1, 3:1, 2.5:1, 2:1, 1.5:1 1, 1:1, etc., preferably 4:1-2:1; the volume ratio of the total volume of ultrapure deionized water used for flushing to the wet resin is 100:1-20:1, for example 100:1, 90:1, 80:1, 70:1, 60:1, 50:1, 40:1, 30:1, 20:1, etc., preferably 80:1-40:1; the ratio of the flushing line speed to the regeneration line speed is 4:1-2:1, for example 4:1, 3.5:1, 3:1, 2.5:1, 2:1, etc., preferably 3:1.
[0041] The water described in steps 1) and 2) is ultrapure deionized water, and the resistivity of the ultrapure water is ≥10MΩ·cm, for example, it is prepared by using a Mili-Q direct pure water machine, including but not limited to resistivities of 10MΩ·cm, 11MΩ·cm, 12MΩ·cm, 13MΩ·cm, 14MΩ·cm, 15MΩ·cm, 16MΩ·cm, 17MΩ·cm, 18MΩ·cm, 19MΩ·cm, 20MΩ·cm, etc., preferably with a resistivity of ≥18.2MΩ·cm.
[0042] In the step 3), the auxiliary agent is selected from one or more of citric acid, tartaric acid, lactic acid, malic acid, maleic acid, malonic acid, lysine, polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, and hexadecyltrimethylammonium bromide, preferably malic acid, lactic acid, or polyethylene glycol; the amount of the auxiliary agent added is 50-2000ppm of the mass of the silicon dioxide in the solution, for example 50ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2100ppm, 2200ppm, 2300ppm, 2400ppm, 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm, 3100ppm, 3200ppm, 3300ppm, 3500ppm, 3600ppm, 3700ppm, 3800ppm, 3900ppm, 4000ppm, 4100ppm, 4200ppm, 4300ppm, 4400ppm, 4500ppm, 4600ppm, 4700ppm, 4800ppm, 4900ppm, 5000ppm, 5100ppm, 5100ppm, 5200ppm, 5300ppm, 5400ppm, 550ppm, 5600ppm, 570 00ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, etc., preferably 500-1000ppm; the stirring time after adding the auxiliary agent is 0.1-10h, for example 0.1h, 0.2h, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h, 8.5h, 9.0h, 9.5h, 10.0h, etc., preferably 1-2h.
[0043] The temperature during exchange in steps 4), 6) and 7) should be controlled at 25-60°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, etc., preferably 40-50°C; the liquid flow rate during downstream flow is controlled at 1-20m / h, for example, 1m / h, 2m / h, 3m / h, 4m / h, 5m / h, 6m / h, 7m / h, 8m / h, 9m / h, 10m / h, 11m / h, 12m / h, 13m / h, 14m / h, 15m / h, 16m / h, 17m / h, 18m / h, 19m / h, 20m / h, etc.
[0044] The inorganic acid in step 5) should be selected from hydrochloric acid, sulfuric acid or nitric acid, preferably hydrochloric acid. The pH after adjustment is 1.0-3.0, such as 1.0, 1.2, 1.5, 1.7, 2.0, 2.2, 2.5, 2.7, 3.0, etc., preferably 1.5-2.0; the stirring time is 0.1-10h, such as 0.1h, 0.2h, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h, 8.5h, 9.0h, 9.5h, 10.0h, etc., preferably 2-4h.
[0045] In the high-purity silica sol prepared by the above method, the concentration of silicon dioxide is 10-50wt%, the particle size is 10-300nm, and the single metal impurity is less than 2ppm.
[0046] The preparation method of the present invention is further explained below by more specific examples, but does not constitute any limitation.
[0047] The main raw materials used in the following examples and comparative examples are as follows:
[0048]
[0049] Detection method:
[0050] The particle size was measured using a ZSU3200 Malvern particle size analyzer.
[0051] The test method for the silicon dioxide content of silica sol refers to HGT 2521-2008 Industrial Silica Sol.
[0052] The concentration of metal ions was measured using an Agilent 7900 ICP-MS.
[0053] Example 1
[0054] The silica content of the ordinary silica sol 1 to be purified is 50wt%, the particle size is 81nm, and the content of some metal impurities is shown in Table 1. The method for purifying the silica sol 1 to obtain the high-purity silica sol 1 is as follows:
[0055] Preparation of high-purity strong acid cation exchange resin: The commercially available strong acid cation exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 5% hydrochloric acid, the regeneration line speed is 1m / h, and the volume ratio of hydrochloric acid used for regeneration to wet resin is 1:1. Then, it is continuously flushed downstream with ultrapure deionized water, the volume ratio of ultrapure deionized water used for flushing to wet resin is 20:1, and the ratio of flushing line speed to regeneration line speed is 2:1. After flushing, a high-purity strong acid cation exchange resin is obtained.
[0056] Preparation of high-purity strong basic anion exchange resin: The commercially available strong basic anion exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 5% sodium hydroxide by mass, the regeneration line speed is 1m / h, and the volume ratio of the sodium hydroxide solution used for regeneration to the wet resin is 1:1. Subsequently, ultrapure deionized water is continuously flushed downstream, the volume ratio of the ultrapure deionized water used for flushing to the wet resin is 20:1, and the ratio of the flushing line speed to the regeneration line speed is 2:1. After flushing, a high-purity strong basic anion exchange resin is obtained.
[0057] Add 50ppm lactic acid to ordinary silica sol 1, stir thoroughly for 0.1h to obtain silica sol A. Let silica sol A flow downstream through a cation exchange column at a flow rate of 20m / h at 60℃, and the effluent is silica sol B. Add 10% hydrochloric acid to silica sol B to adjust the pH of the system to 1.0, stir for 0.1h to obtain silica sol C; let silica sol C flow downstream through a cation exchange column at a flow rate of 20m / h at 60℃, and the effluent is silica sol D. Let silica sol D flow downstream through an anion exchange column at a flow rate of 20m / h at 60℃, and the effluent is high-purity silica sol 1. The contents of some metal impurities are shown in Table 1.
[0058] Example 2
[0059] The silica content of the ordinary silica sol 2 to be purified is 20wt%, the particle size is 300nm, and the content of some metal impurities is shown in Table 1. The method for purifying the silica sol 2 to obtain high-purity silica sol 2 is as follows:
[0060] Preparation of high-purity strong acid cation exchange resin: The commercially available strong acid cation exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 1% sulfuric acid, the regeneration line speed is 10m / h, and the volume ratio of hydrochloric acid used for regeneration to wet resin is 5:1. Then, it is continuously flushed downstream with ultrapure deionized water, the volume ratio of ultrapure deionized water used for flushing to wet resin is 100:1, and the ratio of flushing line speed to regeneration line speed is 4:1. After flushing, a high-purity strong acid cation exchange resin is obtained.
[0061] Preparation of high-purity strong basic anion exchange resin: The commercially available strong basic anion exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 1% potassium hydroxide by mass, the regeneration line speed is 10m / h, and the volume ratio of the sodium hydroxide solution used for regeneration to the wet resin is 5:1. Subsequently, ultrapure deionized water is continuously flushed downstream, the volume ratio of the ultrapure deionized water used for flushing to the wet resin is 100:1, and the ratio of the flushing line speed to the regeneration line speed is 4:1. After flushing, a high-purity strong basic anion exchange resin is obtained.
[0062] 2000ppm malic acid was added to ordinary silica sol 2, and silica sol A was obtained after being stirred for 10 hours. Silica sol A was passed through a cation exchange column at a flow rate of 1m / h at 25°C, and the effluent was silica sol B. 5% sulfuric acid was added to silica sol B to adjust the pH of the system to 3.0, and silica sol C was obtained after being stirred for 10 hours; silica sol C was passed through a cation exchange column at a flow rate of 1m / h at 25°C, and the effluent was silica sol D. Silica sol D was passed through an anion exchange column at a flow rate of 1m / h at 25°C, and the effluent was high-purity silica sol 2. The contents of some metal impurities are shown in Table 1.
[0063] Example 3
[0064] The silica content of the ordinary silica sol 3 to be purified is 10wt%, the particle size is 50nm, and the content of some metal impurities is shown in Table 1. The method for purifying the silica sol 3 to obtain high-purity silica sol 3 is as follows:
[0065] Preparation of high-purity strong acid cation exchange resin: The commercially available strong acid cation exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 4% hydrochloric acid, the regeneration line speed is 2m / h, and the volume ratio of hydrochloric acid used for regeneration to wet resin is 3:1. Subsequently, ultrapure deionized water is continuously flushed downstream, the volume ratio of ultrapure deionized water used for flushing to wet resin is 60:1, and the ratio of flushing line speed to regeneration line speed is 3:1. After flushing, a high-purity strong acid cation exchange resin is obtained.
[0066] Preparation of high-purity strong basic anion exchange resin: The commercially available strong basic anion exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 4% sodium hydroxide by mass, the regeneration line speed is 2m / h, and the volume ratio of the sodium hydroxide solution used for regeneration to the wet resin is 3:1. Subsequently, ultrapure deionized water is continuously flushed downstream, the volume ratio of the ultrapure deionized water used for flushing to the wet resin is 60:1, and the ratio of the flushing line speed to the regeneration line speed is 3:1. After flushing, a high-purity strong basic anion exchange resin is obtained.
[0067] 500ppm polyethylene glycol was added to ordinary silica sol 3, and silica sol A was obtained after being fully stirred for 1h. Silica sol A was passed through a cation exchange column at a flow rate of 2m / h at 45°C, and the effluent was silica sol B. 10% hydrochloric acid was added to silica sol B to adjust the pH of the system to 1.5, and silica sol C was obtained after being stirred for 3h; silica sol C was passed through a cation exchange column at a flow rate of 2m / h at 45°C, and the effluent was silica sol D. Silica sol D was passed through an anion exchange column at a flow rate of 2m / h at 45°C, and the effluent was high-purity silica sol 3. The contents of some metal impurities are shown in Table 1.
[0068] Example 4
[0069] The silica content of the ordinary silica sol 4 to be purified is 40wt%, the particle size is 10nm, and the content of some metal impurities is shown in Table 1. The method for purifying the silica sol 4 to obtain high-purity silica sol 4 is as follows:
[0070] Preparation of high-purity strong acid cation exchange resin: The commercially available strong acid cation exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 4% hydrochloric acid, the regeneration line speed is 2m / h, and the volume ratio of hydrochloric acid used for regeneration to wet resin is 3:1. Subsequently, ultrapure deionized water is continuously flushed downstream, the volume ratio of ultrapure deionized water used for flushing to wet resin is 60:1, and the ratio of flushing line speed to regeneration line speed is 3:1. After flushing, a high-purity strong acid cation exchange resin is obtained.
[0071] Preparation of high-purity strong basic anion exchange resin: The commercially available strong basic anion exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 5% potassium hydroxide by mass, the regeneration line speed is 10m / h, and the volume ratio of the sodium hydroxide solution used for regeneration to the wet resin is 5:1. Subsequently, ultrapure deionized water is continuously flushed downstream, the volume ratio of the ultrapure deionized water used for flushing to the wet resin is 100:1, and the ratio of the flushing line speed to the regeneration line speed is 4:1. After flushing, a high-purity strong basic anion exchange resin is obtained.
[0072] 1000ppm lactic acid was added to ordinary silica sol 4, and silica sol A was obtained after being stirred for 5 hours. Silica sol A was passed through a cation exchange column at a flow rate of 5m / h at 30°C, and the effluent was silica sol B. 7% nitric acid was added to silica sol B to adjust the pH of the system to 2.0, and silica sol C was obtained after being stirred for 5 hours; silica sol C was passed through a cation exchange column at a flow rate of 5m / h at 30°C, and the effluent was silica sol D. Silica sol D was passed through an anion exchange column at a flow rate of 5m / h at 30°C, and the effluent was high-purity silica sol 4. The contents of some metal impurities are shown in Table 1.
[0073] Comparative Example 1
[0074] The silica content of the ordinary silica sol 1 to be purified is 50wt%, the particle size is 81nm, and the content of some metal impurities is shown in Table 1. The method for purifying the silica sol 1 to obtain the high-purity silica sol 5 is as follows:
[0075] Preparation of high-purity strong acid cation exchange resin: The commercially available strong acid cation exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 5% hydrochloric acid, the regeneration line speed is 1m / h, and the volume ratio of hydrochloric acid used for regeneration to wet resin is 1:1. Then, it is continuously flushed downstream with ultrapure deionized water, the volume ratio of ultrapure deionized water used for flushing to wet resin is 20:1, and the ratio of flushing line speed to regeneration line speed is 2:1. After flushing, a high-purity strong acid cation exchange resin is obtained.
[0076] Preparation of high-purity strong basic anion exchange resin: The commercially available strong basic anion exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 5% sodium hydroxide by mass, the regeneration line speed is 1m / h, and the volume ratio of the sodium hydroxide solution used for regeneration to the wet resin is 1:1. Subsequently, ultrapure deionized water is continuously flushed downstream, the volume ratio of the ultrapure deionized water used for flushing to the wet resin is 20:1, and the ratio of the flushing line speed to the regeneration line speed is 2:1. After flushing, a high-purity strong basic anion exchange resin is obtained.
[0077] Ordinary silica sol 1 was flowed downstream through a cation exchange column at a flow rate of 20 m / h at 60°C, and the effluent was silica sol B. 10% hydrochloric acid was added to silica sol B to adjust the pH of the system to 1.0, and silica sol C was obtained after stirring for 0.1 h; silica sol C was flowed downstream through a cation exchange column at a flow rate of 20 m / h at 60°C, and the effluent was silica sol D. Silica sol D was flowed downstream through an anion exchange column at a flow rate of 20 m / h at 60°C, and the effluent was high-purity silica sol 5. The contents of some metal impurities are shown in Table 1.
[0078] Comparative Example 2
[0079] The silica content of the ordinary silica sol 1 to be purified is 50wt%, the particle size is 81nm, and the content of some metal impurities is shown in Table 1. The method for purifying the silica sol 1 to obtain the high-purity silica sol 6 is as follows:
[0080] Preparation of high-purity strong acid cation exchange resin: The commercially available strong acid cation exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 5% hydrochloric acid, the regeneration line speed is 1m / h, and the volume ratio of hydrochloric acid used for regeneration to wet resin is 1:1. Then, it is continuously flushed downstream with ultrapure deionized water, the volume ratio of ultrapure deionized water used for flushing to wet resin is 20:1, and the ratio of flushing line speed to regeneration line speed is 2:1. After flushing, a high-purity strong acid cation exchange resin is obtained.
[0081] Preparation of high-purity strong basic anion exchange resin: The commercially available strong basic anion exchange resin is loaded into an ion exchange column, and regenerated by countercurrent flushing with 5% sodium hydroxide by mass, the regeneration line speed is 1m / h, and the volume ratio of the sodium hydroxide solution used for regeneration to the wet resin is 1:1. Subsequently, ultrapure deionized water is continuously flushed downstream, the volume ratio of the ultrapure deionized water used for flushing to the wet resin is 20:1, and the ratio of the flushing line speed to the regeneration line speed is 2:1. After flushing, a high-purity strong basic anion exchange resin is obtained.
[0082] 50 ppm lactic acid was added to ordinary silica sol 1, and the mixture was stirred for 0.1 h to obtain silica sol A. Silica sol A was passed through a cation exchange column at a flow rate of 20 m / h at 60°C, and the effluent was silica sol B. Silica sol B was passed through a cation exchange column at a flow rate of 20 m / h at 60°C, and the effluent was silica sol D. Silica sol D was passed through an anion exchange column at a flow rate of 20 m / h at 60°C, and the effluent was high-purity silica sol 6. The contents of some metal impurities are shown in Table 1.
[0083] Table 1: Content of some metal impurities in silica sol in the examples and comparative examples (ppm)
[0084]
[0085]
[0086] As can be seen from the above table, the single metal impurity content of the high-purity silica sol obtained by purifying the ordinary silica sol in Examples 1-4 is less than 2ppm. The difference between Comparative Example 1 and Example 1 is that no additional additives are added to stabilize the ordinary silica sol 1 before ion exchange, and the metal impurity content of the high-purity silica sol 5 obtained is significantly increased compared with the high-purity silica sol 1. This is because the solid content of the system is high during the exchange and it has gone through the unstable stage of pH 5-7. The silica sol is prone to partial denaturation or even gelation, so that some metal ions are wrapped and not fully exchanged. The difference between Comparative Example 2 and Example 1 is that there is no acidification after the first cation exchange, which makes the content of Fe, Cu, Ni, Zn and Zr in the obtained high-purity silica sol 6 significantly increased. This is because the hydroxides formed by these ions when the acidity is weak (pH = 3-5) cannot be exchanged.
[0087] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A method for preparing high-purity silica sol by purifying ordinary silica sol, characterized in that: The following steps are involved: 1) Preparation of high-purity strongly acidic cation exchange resin: non-high-purity strongly acidic cation exchange resin is loaded into an ion exchange column, countercurrently regenerated with an acid solution having a mass fraction of 1%-5%, and then flushed with ultrapure water downstream to obtain a high-purity strongly acidic cation exchange resin; 2) Preparation of high-purity strong basic anion exchange resin: non-high-purity strong basic anion exchange resin is loaded into an ion exchange column, countercurrently regenerated with 1%-5% alkali solution by mass fraction, and then flushed with ultrapure water downstream to obtain high-purity strong basic anion exchange resin; 3) Adding an auxiliary agent to ordinary silica sol and stirring thoroughly to obtain silica sol A; 4) passing silica sol A downstream through a cation exchange column filled with high-purity strongly acidic cation exchange resin to perform ion exchange, and the effluent is silica sol B; 5) Adding 5%-10% inorganic acid to silica sol B to adjust the pH of the system, and stirring evenly to obtain silica sol C; 6) The silica sol C is passed downstream through a cation exchange column filled with a high-purity strongly acidic cation exchange resin to perform ion exchange, and the effluent is the silica sol D; 7) The silica sol D is passed downstream through an anion exchange column filled with high-purity strong alkaline anion exchange resin to perform ion exchange, and the effluent is high-purity silica sol.
2. The method according to claim 1, characterized in that In step 1) and step 2), the acid solution is hydrochloric acid or sulfuric acid, and the alkali solution is sodium hydroxide or potassium hydroxide; Preferably, the linear velocity of the acid or alkali solution regeneration is 1-10 m / h, and the volume ratio of the acid or alkali solution to the wet strongly acidic cation exchange resin or strongly basic anion exchange resin is 5:1-1:1, preferably 4:1-2:
1.
3. The method according to claim 2, characterized in that The volume ratio of the total volume of ultrapure water used for rinsing in step 1) and step 2) to the wet strongly acidic cation exchange resin or strongly basic anion exchange resin is 100:1-20:1, preferably 80:1-40:1; Preferably, the ratio of the linear velocity of the ultrapure water flushing to the linear velocity of the acid or alkali solution regeneration is 4:1-2:1, preferably 3:
1.
4. The method according to claim 1 or 3, characterized in that: The ultrapure water in step 1) and step 2) is ultrapure deionized water, and preferably the resistivity of the ultrapure deionized water is ≥10 MΩ·cm, and more preferably the resistivity is ≥18.2 MΩ·cm.
5. The method according to claim 1, characterized in that The auxiliary agent in step 3) is selected from one or more of citric acid, tartaric acid, lactic acid, malic acid, maleic acid, malonic acid, lysine, polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, and hexadecyltrimethylammonium bromide, preferably malic acid, lactic acid, or polyethylene glycol.
6. The method according to claim 1 or 5, characterized in that: The amount of the additive added in step 3) is 50-2000ppm of the mass of silicon dioxide in the ordinary silica sol solution, preferably 500-1000ppm; Preferably, the stirring time after adding the auxiliary agent is 0.1-10 h, preferably 1-2 h.
7. The method according to any one of claims 1 to 6, characterized in that: During the ion exchange in step 4), step 6), and step 7), the temperature is controlled at 25-60°C, preferably 40-50°C; Preferably, the liquid flow rate is controlled at 1-20 m / h in downstream.
8. The method according to any one of claims 1 to 7, characterized in that: The inorganic acid in step 5) should be selected from any one of hydrochloric acid, sulfuric acid or nitric acid, preferably hydrochloric acid.
9. The method according to claim 8, characterized in that The pH of the system is adjusted to 1.0-3.0, preferably 1.5-2.0, using an inorganic acid; Preferably, the stirring time after adjusting the pH of the system is 0.1-10 h, preferably 2-4 h.
10. The high-purity silica sol prepared by the method according to any one of claims 1 to 9, characterized in that: The high-purity silica sol has a silicon dioxide concentration of 10-50wt%, a particle size of 10-300nm, and a single metal impurity of less than 2ppm.
Citation Information
Patent Citations
Purifying method for high-purity silica sol
CN102583406B
A method for treating silica sol
CN104263249B